2006
DOI: 10.1159/000106069
|View full text |Cite
|
Sign up to set email alerts
|

A Dose Escalation Study of Gemcitabine plus Pemetrexed Administered Biweekly in Patients with Solid Tumors

Abstract: Purpose: The study aimed to determine the maximum tolerated doses (MTDs) and identify the dose-limiting toxicities of the biweekly administration of pemetrexed plus gemcitabine in patients with solid tumors. Patients and Methods: Patients with advanced malignancies were treated with escalated doses of gemcitabine and pemetrexed (starting doses 1,250 and 300 mg/m2, respectively) both given on days 1 and 15 in cycles of 4 weeks. Results: Forty-one patients were treated at 7 dose levels. The MTD was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…Sixty-six percent of patients had received two or more chemotherapy regimens before enrollment. The MTD in that trial was gemcitabine 1,750 mg/m 2 plus pemetrexed 450 mg/m 2 , with DLTs related to myelosuppression (13). These results are consistent with the MTDs and toxicity profiles defined in solid tumor and the ovarian cancer cohorts treated in the phase I study reported here.…”
Section: Discussionsupporting
confidence: 82%
“…Sixty-six percent of patients had received two or more chemotherapy regimens before enrollment. The MTD in that trial was gemcitabine 1,750 mg/m 2 plus pemetrexed 450 mg/m 2 , with DLTs related to myelosuppression (13). These results are consistent with the MTDs and toxicity profiles defined in solid tumor and the ovarian cancer cohorts treated in the phase I study reported here.…”
Section: Discussionsupporting
confidence: 82%
“…PMX is approved by the Food and Drug Administration for the treatment of malignant mesothelioma in combination with cisplatin and as a single agent for the treatment of non-small cell lung cancer (18). Moreover, encouraging results were obtained in diverse clinical studies with PMX alone or in combination with other chemotherapeutics (e.g., gemcitabine) to treat a wide range of malignancies (e.g., carcinomas of the ovary, breast, colorectum, head and neck, uterine cervix, and so forth) (18,(24)(25)(26)(27). As structural analogs of folic acid, antifolates use the same transporters to gain entry into the cell interior.…”
Section: Discussionmentioning
confidence: 99%
“…The dose established in this trial was lower than that established in a separate phase I trial for patients with solid tumors [27]. In that phase I trial, an MTD of pemetrexed 450 mg/m 2 and gemcitabine 1,750 mg/m 2 on days 1 and 15 was reached.…”
Section: Discussionmentioning
confidence: 74%